Spatial genetic structure of Salvia japonica Thunb. population (Labiatae) in Botanical Garden of Osaka City University, Kisaichi, Osaka Prefecture, Japan - SUDARMONO SUDARMONO (Society for Indonesian Biodiversity, 2005)
Salvia japonica Thunb. (Japan: Aki-no-Tamurasou) was a perennial herb, protandry insect-pollinated, and self-incompatible with water-flow dispersed seed. We used allozyme loci to know genetic structure of a S. japonica population. We examined spatial autocorrelation of individuals within five distance class with Moran`s I statistics. The area of observation was in plot 5x5 m2 in Botanical Garden of Osaka City University, Kisaichi, Katano, Osaka Prefecture. The 8 loci examined were polymorphic, namely Aat-1, Aat-2, Pgi, Mnr, Pgm-1, Pgm-2, Idh, and 6-Pgd. Low levels of genetic diversity were found for 29 individuals. Ninety-two percent cases for all of distance class were similar and only 8% (8 of 105 cases) were significant differences. This result indicated that the spatial genetic distributions in all of distance classes were all similar and no spatial autocorrelation of genotypes. Only in distance class 2 had one significantly positive cases (0.15) in Pgm-1c, indicating that spatial genetic structure in the study population was weak at most. In the other word that spatial pattern of the individuals within S. japonica population was random. Overall of the result was indicating that genotype among individuals of S. japonica changed distantly and tended to isolation in distance by seed dispersed. Key words: Salvia japonica, spatial autocorrelation, Botanical Garden of Osaka City University, random, isolation, seed.